ANALISIS KESEDIAAN MEMBAYAR JASA LINGKUNGAN DALAM PENGELOLAAN SUMBERDAYA AIR MINUM TERPADU DI INDONESIA (STUDI KASUS DAS CISADANE HULU) - Sutopo, Muhammad Fauzi; Sanim, Bunasor; Saukat, Yusman; Mawardi, Muhammad Ikhwanuddin (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
Ecocentrism paradigm in development are intended to ensure the sustainability ofÃ‚Â water resources in the future for future generations. The research methodology wasÃ‚Â conducted with the model approach to drinking water users willingness to pay forÃ‚Â environmental services (YWTP). The results in Analysis Willingness to Pay in DrinkingÃ‚Â Water Management in the Upstream Watershed Cisadane illustrates that the existenceÃ‚Â of a positive response from drinking water users (entrepreneurs) to be willingness toÃ‚Â pay for environmental services (YWTP) as payment and reward for environmentalÃ‚Â services to the public because it is influenced by the presence and the beneficiaries areÃ‚Â significantly linearly with level of education (sig. 0.041) and Variable in YWTP educationÃ‚Â significant at 95% confidence level. Policy implications of this research that the userÃ‚Â (downstream) is willingness to pay (WTP) for environmental services with averaging Rp1Ã‚Â 538.65 per m3 as payment or reward for environmental services to society (upstream), soÃ‚Â the Government (Local) PES has a potential revenue to fund conservation of Rp106.94Ã‚Â billion per years, but in current conditions the government only earns Rp20.57 billionper year, so that only reached 19.24%.